Teaching speaking with works of art in a preparatory class at university - Ekoc, Arzu (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
Language instructors have been looking for ways to engage their students and encourage speaking. The purpose of this practice-based study is to show that responding to works of art has the potential to foster speaking skills. Apart from familiarizing students with different works of art, it provides an arena for authentic learning and making the most of diversity. We all want to live in a better world where all diversities are cherished, so teaching should be a medium to activate and tolerate different ways of thinking in a respectful manner. In such an activity, teachers can ask questions that require critical thinking skills and creative skills. In this practice-based case study, the researcher, who was also the instructor of two A1 level one-year English preparatory classes at university with a total number of 50 students, started each lesson with five pieces of art and it was observed that even the quietest students expressed their views in English about the paintings. By semi-structured interviews, the researcher found out that it motivated them, colored their day and made them feel outside the classroom. They also stated that it improved their critical thinking and increased their appreciation of art.
Keywords: Language teaching; speaking; paintings; art; works of art; visual literacy; LANGUAGE; ENGLISH; TEACHERS; ANXIETY; Education & Educational Research; Linguistics